The Risk Factors of Refractory Adult-Onset Still’s Disease - Lin Cheng; Hexiang Zong; Dongxu Li; Yaqin Zhang; Long Qian (International Journal of Hepatology)
Conclusion: PLT<314.5×109/L, NLR>10.555, or an AOSD system score of > 5.5 before treatment may serve as independent risk factors for predicting refractory AOSD, providing clinicians with an early warning to identify disease progression.